The Difference in Prevalence of Helicobacter pylori Infectionbetween Chinese and Dayak Ethnics with Dyspepsia Syndrome - Uwan, Willy Brodus; Syam, Ari Fahrial; Lesmana, C. Rinaldi A.; Rumende, C Martin (Jurnal Penyakit Dalam Indonesia, 2016)
Introduction. Helicobacter pylori (H. pylori) infection risk is associated with many factors related to host-agent-environment. Ethnicity is one of the host factors which was the most studied factor overseas. The prevalence of H. pylori infection was found higher in certain ethnic such among Chinese. Based on migration and transmission theory, it was suspected that H. pylori infection was transmitted by people migrating from areas with a high prevalence of infection to the destination area. Chinese in West Borneo are originated from South China region where the prevalence of H. pylori infection is high. It is estimated that there are differences in the prevalence of H. pylori infection among Chinese compared to the native people of West Borneo, the Dayaknese. Methods. This was a cross-sectional study to determine the differences in the prevalence of H. pylori infection. The study was conducted at St. Antonius General Hospital Pontianak from December 2014 to June 2015 with consecutive sampling method. H. pylori infection prevalence is presented in percentage numbers, while the epidemiological characteristics and endoscopic finding differences among Chinese and Dayaknese were analyzed by bivariate analysis using the chi-square with significance value (p) = 0.05. Results. From a total of 203 subjects in this study, consisted of 102 Chinese subjects and 101 Dayaknese subjects, the prevalence of H. pylori infection was 40.8%. The prevalence among Chinese is higher than Dayaknese, which is 48.0% and 33.7%, respectively. There is no difference in the epidemiological characteristics and endoscopic findings in both ethnic groups. Conclusions. The prevalence of H. pylori infection among the Chinese (48.0%) is higher than among Dayaknese (33.7%). There is no difference in the epidemiological characteristics and endoscopic findings among both ethnic groups.